Perancangan Desain 3D dan Analisis Struktur Meja Industri Menggunakan Metode Finite Element Analysis - Saputra, Gading Arya (Engineering Faculty at Universitas Singaperbangsa Karawang, 2024)
The differential carrier is one of the components of heavy automotive vehicles, such as trucks, manufactured by PT XYZ. Alongside the production capabilities, the manufacturing of differential carriers requires proper production facilities, one of which is the industrial table. The industrial table at PT XYZ is utilized as a platform for placing components and transferring them from the production area to the inspection section. Differential carriers have a relatively large mass, and each month, there are 10 to 20 repair or replacement orders for industrial tables and shutters due to structural failures. Therefore, a structural design and strength analysis are needed to prevent failures that may endanger workers. This study employs the stress analysis method to determine the structural strength of the frame. Based on the analysis using AISI 1050 carbon steel, the results showed a maximum Von Mises stress of 39.5951 MPa, a 1st principal stress of 41.0076 MPa, a maximum 3rd principal stress of 7.94286 MPa, a maximum displacement of 0.304201 mm, and a minimum safety factor of 5.22393. Meanwhile, the analysis using Stainless Steel 202 yielded a maximum Von Mises stress of 39.7617 MPa, a 1st principal stress of 41.06 MPa, a maximum 3rd principal stress of 7.77192 MPa, a maximum displacement of 0.298047 mm, and a minimum safety factor of 10.3694. The analysis results indicate that Stainless Steel 202 performs better compared to AISI 1050 Steel.